OCEANS 2011 IEEE - Spain 2011
DOI: 10.1109/oceans-spain.2011.6003480
|View full text |Cite
|
Sign up to set email alerts
|

High performance underwater UHF radio antenna development

Abstract: This study presents the development of a UHF radio antenna for underwater transmissions in order to rapidly transmit large size files and real-time video.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…We can observe that, as it was observed for freshwater, the specific attenuation factor is underestimated. That deviation was also pointed out in [17][18] at 2.4 GHz, and the authors found that the empirical data in [12] estimates an additional loss of 4 dB/cm that must be sum to the estimated factor. That result was also confirmed for our working conditions at 2.4 GHz, but not in the whole range of frequencies of the study.…”
Section: B Resultssupporting
confidence: 52%
“…We can observe that, as it was observed for freshwater, the specific attenuation factor is underestimated. That deviation was also pointed out in [17][18] at 2.4 GHz, and the authors found that the empirical data in [12] estimates an additional loss of 4 dB/cm that must be sum to the estimated factor. That result was also confirmed for our working conditions at 2.4 GHz, but not in the whole range of frequencies of the study.…”
Section: B Resultssupporting
confidence: 52%
“…Research in the field of underwater communications continues to generate a lot of interest worldwide, due to a wide range of applications that this technology covers, which include: offshore oil and gas field monitoring, coastline protection and surveillance, oceanographic data collection which will require data exchange between two or more Autonomous Underwater Vehicles (AUVs) and underwater environmental observation for exploration [1,2]. It is also a known fact that acoustic and ultrasonic systems have been a standard technology for underwater communications as they are typically good for long range communications (up to tens of kilometers).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this attenuation feature could be beneficial for short-range subsea applications, because it ensures non-interference with other EM signals. Recently, some developments have shown that the 2.4 GHz band is of tremendous interest for several configurations [12][13][14]. Previous studies have demonstrated the potential of this band in terms of signal propagation under several conditions [15,16].…”
Section: Introductionmentioning
confidence: 99%